Effect of Pottery Irrigation and Mulching on Melon (Cucumis melo) Growth and Soil Properties of Alfisol and Entisol - Rahayu, Rahayu; komariah, komariah; Pujiyarti, Mei (JOURNAL OF TROPICAL SOILS, 2022)
The water supply in dry land depends on the rainfall, which causes agricultural constraints and limited water supply. The pottery irrigation method is considered capable of overcoming water shortages during the dry season. Pottery irrigation uses porous clay, so the water slowly comes out of the pottery and wet the surrounding soil. The research aimed to study the influence of pottery subsurface irrigation with and without mulching on watermelon growth and soil properties of clayey soil Alfisol and sandy soil entisol. The research was conducted on July 2019 in the experimental field Faculty of Agriculture, Karanganyar Regency. The experimental research design used a nested design with a 3-factor treatment that were soil type (T), fertilization method (P), and use of mulch (M). The types of soil were Alfisol (T1) and Entisol (T2). The fertilization methods were fertigation 100% (P1), fertigation 50% (P2), and banding fertilization 100% (P3). Mulch application included control, without mulch (M0) and mulch (M1). The combination of P1M1 treatment on alfisol and entisol soil showed the highest soil moisture with values of 23.1% and 22.5%, respectively. The highest fruit weight of melon in alfisol and entisol soils were indicated by the same treatment (P1M1) with values of 580.33 g and 616.5 g, respectively.